The Evolution and Future of DAOs: Embracing AI and New Technologies - Shi, Jianzheng (Technium: Romanian Journal of Applied Sciences and Technology, 2023)
Decentralized Autonomous Organizations (DAOs) represent a paradigm shift in the realm of organizational structures, leveraging blockchain technology to operate autonomously through smart contracts and collective decision-making. This article delves into the evolution and potential future of DAOs, emphasizing the integration of Artificial Intelligence (AI) and emerging technologies. Drawing from seminal literature, the article underscores the transformative potential of DAOs in reshaping organizational governance, contract formulation, and decentralized operations. The integration of AI promises enhanced efficiency, predictive insights, and a personalized member experience. As DAOs evolve, they are poised to redefine the fabric of organizational design and operation in the digital age.